Anaesthetists' knowledge of South African law pertaining to informed consent - Mamoojee, Anisah Ismail (My University, 2018)
Lack of knowledge of the law places a medical practitioner at risk of litigation. Research has shown that medical personnel’s knowledge of law and their consent taking practices are inadequate. This prospective, contextual, descriptive study aimed to determine the University of the Witwatersrand (WITS) anaesthetists’ knowledge of South African Law pertaining to informed consent. 167 willing anaesthetists answered 10 multiple choice questions (n=167) and the mean score achieved was 60.09% (SD 12.61%). The question testing The Mental Health Care Act No. 17 of 2002 achieved the highest mean score of 88.92% (SD=22.22%) while the questions testing The Children’s Act No. 38 of 2005 achieved the lowest mean score of 51.82% (SD=17.84%). Knowledge of The Choice of Termination of Pregnancy Act No. 92 of 1996 worsened with increasing years after graduation from medical school (p=0.0013) while knowledge of The Children’s Act No. 38 of 2005 correlated positively with professional designation (p=0.0004), increased years of anaesthetic experience (p=0.0180) and attendance at formal postgraduate teaching on informed consent (p=0.0080). Improved knowledge of The National Health Act No. 61 of 2003 correlated with higher professional designation (p=0.0120). Knowledge of The Mental Health Care Act No. 17 of 2002 (p=0.0276) and of The Sterilisation Act No. 44 of 1998 (p=0108) worsened with increasing years after graduation from medical school. Professional designation correlated with overall mean questionnaire score (p=0.0163), with those of higher professional designation performing better. This study revealed that formal postgraduate teaching on informed consent correlated with a higher mean questionnaire score and, by implication, improved knowledge. The mean score in the group of participants that had not attended formal postgraduate teaching on informed consent was lower than the group that had attended. Educational interventions to improve knowledge should be instituted to provide an optimal service to the patient and to reduce the burden of medicolegal claims.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Anaesthesiology, Johannesburg, 2018
Keywords: Medical ethics; Patients--legal status, laws, etc.